COMPARISON OF ISLAMIC ECONOMY AND CONVENTIONAL ECONOMY TO PEOPLE'S INCOME GROWTH IN REDUCING POVERTY AND UNEMPLOYMENT - Tarmizi Tarmizi (Teunuleh Publisher, 2020)
Islamic economic system is built on the foundation of the Islamic faith, the faith in question is the right because it comes from Allah brought to mankind through the prophet Muhammad. The Islamic faith is a faith that satisfies reason, reassures the soul, and is in accordance with human nature. In an individual context, economic activity is based on the values of worship. The economic system known by society globally is the capitalist and socialist economic system. In the economic context, both systems have been able to increase the prosperity of the people in the country that uses both economic systems. The capitalist system is influenced by the zeal to make the most of its profits with limited resources. This capitalist venture is supported by the values of freedom to make ends meet. This freedom resulted in high competition among others in defense, while the socialist economic system had the goal of mutual prosperity. In conclusion, the Islamic economic system is a solution economic system for various problems that have arisen, while the conventional economic system is an economic system that is widely used by various countries in the world, including Indonesia. A conventional economy is an economic system that gives full freedom to everyone to carry out economic activities.